2014
DOI: 10.3233/nre-141110
|View full text |Cite
|
Sign up to set email alerts
|

Temporal recovery of activities of daily living in the first year after ischemic stroke: A prospective study of patients admitted to a rehabilitation unit

Abstract: BACKGROUND: The ability to perform basic activities of daily living (ADL) independently is a marker of functional recovery after a stroke. However, there few studies documenting their long-term recovery. OBJECTIVE: To document temporal recovery of activities of daily living (ADL) and establish predictors of ADL in a cohort of ischemic stroke patients in the first year after stroke. METHODS: Prospective cohort study of 163 patients with first-ever ischemic stroke admitted to a rehabilitation centre. The Modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Another study using the modified Rankin Scale (mRS) did not compare functional recovery between age groups [ 16 ]. A third study found a negative effect of age on functional recovery in univariate analysis; however, it did not uncover a specific age for functional decline [ 17 ]. However, animal study results revealed age may be a barrier for plasticity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study using the modified Rankin Scale (mRS) did not compare functional recovery between age groups [ 16 ]. A third study found a negative effect of age on functional recovery in univariate analysis; however, it did not uncover a specific age for functional decline [ 17 ]. However, animal study results revealed age may be a barrier for plasticity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the scores of the CPT and the CRT in the acute stage were independent predictors for δMBI at post-stroke 3 months along with other variables such as age, initial K-MBI and FMSA, while MMSE was not significantly related. It is generally accepted that recovery of most of the MBI score occurs by 3 months after stroke [ 30 ], hence, subjects in this study showed significantly higher K-MBI at 3 months after stroke, as compared to initial evaluation. The current study included 10 subjects whose K-MBI were assessed at post-stroke 6 months, but there was no significant increase in K-MBI at 6 months, as compared to that of post-stroke 3 months.…”
Section: Discussionmentioning
confidence: 81%
“…This result supported by Tveiten et al, (2014), who reported that considerable improvement from acute stroke had taken place during these periods, particularly between the time of discharge and 1 month. This early improvement can be attributed to the spontaneous neurological processes Kong and Lee (2014). This occurs within 3 months after stroke Between 6 months and 2 years post-acute stroke, the Barthel Index score still improves but not considerably.…”
Section: Discussionmentioning
confidence: 93%